Bagong tahanan a model for regional agro-housing and livelihood communities - Ravago, Matthew Geo N. (College of Architecture, University of the Philippines Diliman, 2019)
The thesis stems from three main issues, primarily negligent urbanization which augments the issues of poor living conditions and scarcity of agricultural lands. It focuses on how these developments have most greatly affected the poorest in our population. Presently, there are numerous independent developments that have made progress in uplifting the lives of these families; but many programs, specifically in housing, while able to provide shelter, still leave much to be desired. Lacking access to utilities, open space and a healthy environment, these projects turn into slums and further exclude the residents from the rest of society. In order to address the issues mentioned, the research proposes a design for a new housing model that targets low-income informal settler families, particularly those in rural settings. In terms of program, it will comprise an affordable agro-housing complex with an integrated livelihood center. The housing model is segregated into three distinct phases with each tackling distinct concerns mirroring and bringing about the different stages of growth the families themselves will go through ; in its totality, it envisions a more mindful approach to housing that is increasingly more participatory, inclusive and grounded to the individual needs of each community. It seeks to use responsible housing as a proactive rather than reactive tool to mitigate negligent urbanization through targeting these rural communities and bringing them to a more balanced urban form.